Very high-resolution infrared imagery of misaligned tungsten monoblock edge heating in the WEST tokamak. (June 2021) - Grosjean, A.; Corre, Y.; Gaspar, J.; Gunn, J.P.; Carpentier, S.; Courtois, X.; Dejarnac, R.; Delmas, E.; De Temmerman, G.; Diez, M.; Dubus, L.; Dupont, L.; et al.
Abstract: Fourteen ITER-like plasma-facing units (PFUs) made of bulk tungsten were installed in the WEST tokamak divertor. Five of which were misaligned with their poloidal leading edges (LEs) exposed to the plasma heat flux: two sharp-edge PFUs and three chamfered PFUs (vertical misalignment h = 0.30 ± 0.1 mm). The parallel heat flux is measured on the outer strike point with a very high-resolution (VHR) infrared camera, featuring a sub-millimeter spatial resolution ( 0.1 mm/pixel). A Medium Wavelength IR filter (MWIR) was used to lower the temperature detection threshold (Tthreshold, BB ≈ 250 °C) and extend the IR analysis to the full toroidal Monoblock (MB) length on both outer (OSP) and inner (ISP) strike points. The parallel heat flux derived from the VHR data ( 70 MW/m 2 ) is consistent with previous analysis and other measurements (Thermocouple and Fiber Bragg Grating) at the maximum heat flux location (OSP). This corresponds to real temperatures of about 1000 °C on the LE. Values obtained on the LE of the ISP are typically lower than of the OSP by a factor of two. However, a significant discrepancy between modeling and measurement is observed along with the toroidal temperature profile, with a temperature drop in the first 5 mm after the LEs. Visual and microscopic analysis performed on the component show clear evidence of surface state modification caused by plasma exposure: the presence of cracks on the LE, polished surface in its vicinity, and rougher surfaces further away from the LE.